(untitled) (Bangladesh Journal of Animal Science, 2014)
The experiment was conducted to examine the effect of freezing and defrosting methods on the quality of beef. Two types of beef samples named as fresh and cured beef samples were taken. Both types were divided into three sub divisions namely air, water and microwave oven. These samples were stored at -20°C temperature in the freezer for 90 days and analyzed on 10th, 45th and 90th day. The dry matter, crude protein, ether extract and ash percentages and standard plate count (SPC) were differed significantly (p<0.01) among the air, water and microwave defrosted samples. Up to 90th days of freezing at -200C dry matter content increased with the increase of storage time almost in all samples except microwave fresh samples. The protein content decreased with the increase of storage time from 10 to 45 days but increased from 45 to 90 days. The ash content decreased with the increase of storage time in case of fresh frozen samples but increased with the increase of storage time in case of cured frozen samples except microwave oven cured sample. Ether extract value gradually increased with the increasing of storage period in case of air fresh, water fresh, air cured and water cured frozen samples but decreased with the increasing of storage period in case of microwave oven fresh and microwave oven cured samples. The SPC value increased with the increase of storage time in case of all samples and differed significantly (p<0.01) among the parameters. The cured microwave defrosted beef was proved as the best technique of defrosting frozen beef. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21649 Bang. J. Anim. Sci. 2014. 43 (3): 202-206